2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7590861
|View full text |Cite
|
Sign up to set email alerts
|

Improving test-retest reliability of quantitative electroencephalography using different preprocessing approaches

Abstract: This work aims to assess the effect of preprocessing approaches over test-retest reliability of quantitative electroencephalography measurements. Two electroencephalography sessions were recorded during an eyes-closed resting state condition in 15 young healthy individuals. The second session was 4 to 6 weeks after the first one. Clean recordings were obtained from the implementation of different preprocessing approaches commonly used in the literature. We then estimated the power spectrum density, for each in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…EEG power for mid-range frequencies (theta, alpha, and beta, as opposed to delta and gamma; Ip et al, 2018) and relative power (as opposed to absolute power; Salinsky et al, 1991) have shown correlation coefficients >0.8 for EEG sessions a few weeks apart; this is in the range of test-retest correlations for commonly used tests of cognitive ability (Elliott, 2007;Canivez and Watkins, 1999). Methodological advances in EEG preprocessing, such as a robust reference to average and wavelet independent component analysis which act to attenuate the effects of data collection artifact, improve test-retest reliability in higher frequency bands such as beta and gamma (Suarez-Revelo et al, 2016). However, the reliability of these features in children with or without neurodevelopmental disabilities remains unmeasured.…”
Section: Introductionmentioning
confidence: 94%
“…EEG power for mid-range frequencies (theta, alpha, and beta, as opposed to delta and gamma; Ip et al, 2018) and relative power (as opposed to absolute power; Salinsky et al, 1991) have shown correlation coefficients >0.8 for EEG sessions a few weeks apart; this is in the range of test-retest correlations for commonly used tests of cognitive ability (Elliott, 2007;Canivez and Watkins, 1999). Methodological advances in EEG preprocessing, such as a robust reference to average and wavelet independent component analysis which act to attenuate the effects of data collection artifact, improve test-retest reliability in higher frequency bands such as beta and gamma (Suarez-Revelo et al, 2016). However, the reliability of these features in children with or without neurodevelopmental disabilities remains unmeasured.…”
Section: Introductionmentioning
confidence: 94%
“…In 2017, Shirk et al [ 39 ] tested the impact of subjective artifact removal on Event-Related Potential (ERP) results, estimating the inter-rater reliability of different subjective signal-cleaning approaches. The test–retest study by Suarez-Revelo and colleagues [ 40 , 41 ] compared different pre-processing of resting state EEG for the estimation of spectral power in six frequency bands. For specific MWL correlates estimation, a test–retest study was conducted in 2021 by Getzmann et al [ 42 ] to assess the performance of the cEEGrids recordings, which are based on C-shaped electrode arrays positioned around the ear.…”
Section: Related Workmentioning
confidence: 99%
“…Interestingly, reliability was most robust for the alpha and theta bands (Suarez-Revelo et al, 2016). Thus, it is recommendable to test the influence that any newly developed toolbox exerts on raw EEG data ideally by comparing it to both human-dependent approaches and other established automated programs on a variety of datasets before implementing it on a formal study.…”
Section: Beyond Psychologymentioning
confidence: 99%